Effectiveness of the training courses of kindergarten teachers in Riyadh in the development of their professional qualifications - Al-Zawad, Nuf Abdullah (Journal of Educational and Psychological Sciences, 2017)
The aim of this study was to investigate the effectiveness of the training courses of kindergarten teachers. The study used the descriptive method. The target population of the study was 46 trainees from the training center of kindergartens, teachers and kindergartens in Riyadh. In this study, three tools were used to collect the information, namely, the questionnaire and the training impact form within the training bag of the center and the interview. The study also presented four questions. This study draws on the importance of the local and international approach to the issues of early childhood and the associated educational programs and the training of teachers. And the importance of the educational process, which is the teacher one of the elements or pillars of effective and the importance of the early stage of education as it is the basic stage in which the formation of knowledge and information of the child.Also contribute to the development and renewal of the teacher’s experiences through training programs both during the service or rehabilitation programs and programs aimed at developing and renewing the teacher’s experiences . It also helps to compensate for the lack of studies and researches related to training programs and the measurement of their results, especially those programs provided to kindergarten teachers. The main findings of the study are that there is a correlation between the training program and the future of the trainees. And contributes to the identification of the characteristics of growth in kindergartens where the average arithmetic (3). The program offers suggestions to deal with the behavioral class problems of the child and contribute to the identification of ways to observe the behavior and modify it in addition to the administrative supervision p To the course contributed to the achievement of its objectives, where the average arithmetic mean (2.93). The results showed high approval of the planning axis of the educational unit with an average of (4.09) and high approval of the axis of dealing with children with an average of (4.29). As for the most important obstacles, it was easy to reach the training center where it reached the average of (2.26) and the candidates for training on the training program well ahead of time with an average of (2.30). The study recommended ways to increase the effectiveness of the training center for kindergartens teachers and work to remove the obstacles that limit the enrollment of private sector teachers such courses .